Philip Diamond (with Jackie Hunt): Covent Garden Fish Book - D., J.M. (Petits Propos Culinaires, 1992)
Philip Diamond (with Jackie Hunt): Covent Garden Fish Book: Kyle Cathie, London, 1992: some colour illustrations for identification purposes, bibliography and index, 248 pp, P/B £9.99.